Optimalisasi Pengamanan Aset Tetap: Strategi untuk Meningkatkan Pengakuan Tanah dan Bangunan sebagai Aset yang Sah - Rizkiatanta, Brillianggita Kindred; Djasuli, Mohamad (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2023)
This article aims to find out the optimization of fixed asset security and the recognition of land and buildings as legal assets in Bangkalan Regency. In order to approach this problem, reference is made to the Regulation of the Minister of Home Affairs Number 19 of 2016 concerning Guidelines for the Management of Regional Assets. The data were collected through interviews with the BPKAD of Bangkalan Regency which then the data will be analyzed qualitatively. This study concludes that the implementation of asset security has not been optimal, both in terms of administrative security, physical security and legal security. This is indicated by the large number of land and buildings that are still in the process of submitting for certification, land and buildings that are recognized as owned by other parties, and percaton land. All land assets must be certified on behalf of the Regional Government, put up a land layout mark by making a boundary fence, put up a sign of land ownership, and maintain it so that efforts can be made to maximize the assets to become legal assets.